Heat-resistant high borosilicate glass and preparation method thereof
By using high heat -resistant modifiers with siliconized cymbal, sodium sodium silicate, composite melting agent with sodium spang, sodium fluorine, lithium borate salt, and nickel nickel, and molybdenum acid, six, six The composite clarine of sodium fluorine and the easy -to -sublime divisions solves the problem of insufficient thermal thermal resistance of high borosilica glass, and realizes efficient heat resistance.
Patent Information
- Application Number
- CN202411642544.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-18
AI Technical Summary
The existing high borosilicate glass has poor heat resistance, especially the upper limit temperature of thermal shock resistance and few cycles of thermal shock resistance, which is difficult to meet the actual use requirements.
It uses a high heat-resistant modifier composed of zirconium silicide and sodium zirconosilicate, combined with a composite flux composed of zirconate, sodium fluoroaluminate, lithium borate, nickel boride, as well as molybdate and sodium hexafluoroantimonate. , a composite clarifier composed of easily sublimable decomposition products, and through optimizing the formula and process flow, high borosilicate glass with low linear expansion coefficient and excellent thermal shock resistance is prepared.
The heat resistance of high borosilicate glass has been significantly improved. The linear thermal expansion coefficient is 3.15~3.31×10-6/K, the number of thermal shock resistance cycles is 32~37 times, and the upper limit temperature of thermal shock resistance cycle is 590~610℃, which meets the requirements meet higher heat resistance requirements.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to heat-resistant high-borosilicate glass and a preparation method thereof, belonging to the technical field of glass production. Background Art
[0002] Borosilicate glass has remarkable characteristics, especially excellent thermal properties, chemical stability, good mechanical properties, and high visible light transmittance. It has been widely used in instruments, utensils, solar vacuum, lamps, etc. However, due to the particularity of the high borosilicate component in borosilicate glass and the high content of network-forming oxides in the glass, it is difficult to clarify, easy to separate phases, has a high melting temperature, and has high viscosity at high temperatures. The high borosilicate glass obtained in actual large-scale production does not have ideal thermal properties, especially heat resistance, which does not meet the actual use requirements.
[0003] Chinese patent CN111559863A discloses a heat-resistant and corrosion-resistant high borosilicate brown glass and a preparation method thereof, wherein the brown glass is a pre-treated substrate with a modified film layer on the surface, the pre-treated substrate is obtained by etching the surface of the glass substrate, and the components of the glass substrate include silicon dioxide, boron oxide, antimony oxide and other components, wherein silicon dioxide is used as a skeleton component of the glass, which can improve the chemical stability and durability of the glass, and components such as boron oxide and aluminum oxide can greatly improve the chemical stability of the glass and improve the mechanical properties of the glass; the invention discloses a heat-resistant and corrosion-resistant high borosilicate brown glass and a preparation method thereof, the process design is reasonable, the component ratio is appropriate, and the prepared brown glass has excellent mechanical properties, good hydrophobicity, corrosion resistance, excellent chemical stability, and high practicality. In terms of heat resistance, the high borosilicate brown glass obtained in the patent only tests the linear expansion coefficient at 300°C to meet the actual requirements of 3.32~3.35, and does not fully pay attention to key heat resistance performance indicators such as the number of thermal shock resistance and the upper limit temperature of thermal shock resistance.
[0004] Chinese patent CN111574050A discloses a preparation process of a high-heat borosilicate glass product, which includes the following components by weight: 61-75 parts of SiO2, 12-22 parts of B2O3, 0.5-4 parts of Al2O3, 0.5-3.5 parts of Na2O, 2.5-8.5 parts of K2O, 0.8-3.3 parts of MgO, 0.3-1.6 parts of CaO, 0.2-0.7 parts of SrO, 0.8-3.1 parts of ZrO2, 0.5-1.2 parts of NaCl, and 0.1-0.2 parts of CeO2. The high-heat borosilicate glass product provided by the present invention has a low thermal expansion coefficient and excellent thermal shock resistance; it can not be broken under a sudden temperature change of -20-120°C. The high borosilicate glass products obtained from this patent only have a low thermal expansion coefficient, and the thermal shock resistance has only been tested within a small temperature range of -20~120℃, which makes it difficult to prove that they have good thermal shock resistance.
[0005] From the above, we can see that the heat resistance of high borosilicate glass is still relatively poor, which is mainly reflected in the low upper limit temperature of thermal shock resistance and the small number of thermal shock resistance cycles. Therefore, the development of high borosilicate glass with excellent heat resistance is still a long and arduous task. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides a heat-resistant high-borosilicate glass and a preparation method thereof, so as to achieve the following invention objectives: to prepare high-borosilicate glass with low linear expansion coefficient and excellent thermal shock resistance.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A heat-resistant high borosilicate glass and a preparation method thereof, wherein the specific formula of the heat-resistant high borosilicate glass is, in parts by weight:
[0009] 66~83 parts of silicon dioxide,
[0010] Boron trioxide 15-25 parts,
[0011] 5-9 parts of sodium oxide,
[0012] 2~4 parts of aluminum oxide,
[0013] 1~4 parts of composite flux,
[0014] 0.5~1.5 parts of composite clarifier,
[0015] 2~6 parts of high heat resistance modifier;
[0016] The composite flux is composed of zirconate, sodium fluoroaluminate, lithium borate and nickel boride;
[0017] The zirconate is one of lithium zirconate and sodium zirconate;
[0018] The lithium borate salt is one of lithium metaborate and lithium tetraborate;
[0019] The mass ratio of the zirconate, sodium fluoroaluminate, lithium borate and nickel boride is 10-50:5-19:15-40:3-9;
[0020] The composite clarifier is composed of molybdate, sodium hexafluoroantimonate, and easily sublimable decomposition products;
[0021] The molybdate is one of sodium molybdate, lithium molybdate and potassium molybdate;
[0022] The easily sublimable decomposition product is one of molybdenum dioxide and aluminum titanate;
[0023] The mass ratio of the molybdate, sodium hexafluoroantimonate, and the easily sublimable decomposition product is 15-60:2-8:6-14;
[0024] The following are further improvements to the above technical solution:
[0025] Step 1: Preparation of high heat resistant modifier
[0026] Zirconium silicide and sodium zirconium silicate are mixed in a mass ratio of 20-80:35, and put into a planetary ball mill. Grind at a speed of 600-1600 rpm for 60-90 minutes to obtain a coarse abrasive. Dry the coarse abrasive in an oven at 200-260°C for 10-16 hours, then put into the planetary ball mill again, and ball-mill at a speed of 1700-2600 rpm to a particle size of 0.01-0.1 μm. Discharge the material to obtain a high heat-resistant modifier.
[0027] Step 2: Preparation of heat-resistant borosilicate glass
[0028] According to the specific formula of heat-resistant high borosilicate glass in parts by weight, weigh the corresponding mass of silicon dioxide, diboron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, high heat-resistant modifier and other powdered raw materials, mix these powders preliminarily, put them into a zirconia crucible, and then heat up to 1000~1300℃ at a rate of 3~6℃ / min and keep it warm for 25~45 minutes, then heat up to 1720℃ at a rate of 1~4℃ / min. ~1860℃ and keep it warm for 2~3 hours, then cool it down to 1500~1600℃ and keep it warm for 25~40 minutes, then pour the 1500~1600℃ glass liquid into the graphite mold for molding, preheat the graphite mold to 850~1000℃ in advance, maintain the temperature of 850~1000℃ for annealing, after annealing for 2~3 hours, cool it down to room temperature at a rate of 1~3.5℃ / min, polish the surface after demolding, and obtain heat-resistant high borosilicate glass.
[0029] Compared with the prior art, the present invention achieves the following beneficial effects:
[0030] 1. The present invention uses a high heat-resistant modifier composed of zirconium silicide and sodium zirconium silicate to improve the high heat resistance of high borosilicate glass. Sodium zirconium silicate is a commonly used glass modifier. After melting, sodium zirconium silicate will dissociate into silicate ions and zirconium ions. The zirconium ions will be embedded in the boron oxygen triangular structure in the glass network, inducing the triangular structure to form a more compact boron oxygen tetrahedron structure. The anion network group formed by the silicate ions and the silicon oxygen tetrahedron formed during the melting of the glass raw materials can form a more compact and firm three-dimensional skeleton structure. This three-dimensional skeleton structure and the boron oxygen tetrahedron The structure makes the borosilicate bond more firm and dense, and the addition of zirconium silicide will generate more zirconium ions and free silicon ions in the entire glass melting reaction material system under high temperature conditions of 1600℃ and above. These zirconium ions and silicon ions will increase the above-mentioned induction effect and the amount of silicate ions generated (silicon ions are unstable and easily capture free oxygen and oxygen-containing oxidizing substances in the glass melting material system to generate silicate ions), further enhancing the skeleton density and bonding strength of the high borosilicate glass network, and ultimately promoting a significant improvement in the heat resistance of high borosilicate glass.
[0031] 2. The present invention uses a composite flux composed of zirconate, sodium fluoroaluminate, lithium borate and nickel boride to reduce the viscosity of the raw materials of high borosilicate glass when they are melted, and promote the uniform mixing of the raw materials under high temperature. The melting points of zirconate and lithium borate are between 800 and 1000°C, and the melting points of sodium fluoroaluminate and nickel boride are around 1000°C. Compared with the melting temperature of high borosilicate glass above 1600°C, the melting points of these substances in the above flux are relatively low, and the zirconate ions released after the zirconate is melted and the lithium borate melt The borate ions and lithium ions released after melting have no negative impact on the glass network after the high borosilicate glass is solidified. These ions can be relatively well embedded in the network structure of the boron-oxygen tetrahedron and silicon-oxygen tetrahedron inside the high borosilicate glass. Therefore, these components contained in the composite flux of the present invention achieve the goal of reducing the viscosity of the glass raw material melt without introducing any components that have any negative impact on the performance of the high borosilicate glass. Therefore, the composite flux added in the present invention plays an extremely important role in improving the heat resistance of the final high borosilicate glass product.
[0032] 3. The present invention uses a composite clarifier composed of molybdate, sodium hexafluoroantimonate, and easily sublimable decomposition products to effectively discharge bubbles generated during the entire melting process of high-borosilicate glass raw materials. Sodium hexafluoroantimonate in the composite clarifier is a relatively common glass additive, which is often used in the manufacture of high-grade glass. Its cost is relatively high. It has a relatively good clarification effect on non-high-borosilicate glass. However, for high-borosilicate glass with very high melting viscosity at high temperatures, the clarification effect of sodium hexafluoroantimonate does not always improve with the increase in the amount of addition, but has a certain upper limit. Therefore, in the composite clarifier designed by the present invention, the amount of sodium hexafluoroantimonate added is relatively small. The present invention mainly utilizes the low melting point of molybdate and the low viscosity of molybdate after melting to reduce the viscosity of the glass raw materials in the low-temperature melting stage, so that the large bubbles formed in the low-temperature stage can be discharged from the inside of the glass melt in time, thereby avoiding the large bubbles from breaking into small bubbles when the high-temperature fluidity of the glass melt is enhanced and becoming more difficult to discharge. In addition, the molybdate melt The molybdate radicals dissociated after melting have a certain charge interaction with boron oxide, which can effectively reduce the boron volatilization problem in the high-temperature process of the glass melt and reduce the changes in the proportion of the main raw materials of the borosilicate glass caused by the volatilization of boron. The two easily sublimated decomposition products, molybdenum dioxide and aluminum titanate, added to the composite clarifier mainly utilize the strong sublimation or decomposition effect of these two substances above 1000°C to promote the melting and discharge of small bubbles in the high-temperature glass melt above 1000°C, that is, utilize the high-temperature sublimation and strong decomposition effect of the above two substances to promote the aggregation and growth of small bubbles in the high-temperature glass melt and the smooth rupture and escape of small bubbles after they become large bubbles. This process is similar to fully stirring the high-temperature glass melt to promote the rapid melting and discharge of small bubbles inside. Based on the above discussion, the composite clarifier composed of molybdate, sodium hexafluoroantimonate, and easily sublimated decomposition products in the present invention has a very good clarification effect, and finally improves the high heat resistance of high borosilicate glass.
[0033] 4. The heat-resistant borosilicate glass obtained by the present invention has a linear thermal expansion coefficient of 3.15~3.31×10 -6 / K, the number of thermal shock resistance cycles is 32~37 times, and the upper limit temperature of thermal shock resistance cycles is 590~610℃. DETAILED DESCRIPTION
[0034] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0035] Example 1: A method for preparing heat-resistant high borosilicate glass
[0036] Step 1: Preparation of high heat resistant modifier
[0037] Zirconium silicide and sodium zirconium silicate were mixed in a mass ratio of 60:35, and put into a planetary ball mill. The mixture was coarsely ground at a speed of 1100 rpm for 80 minutes to obtain a coarse abrasive. The coarse abrasive was dried in an oven at 240°C for 15 hours and then put into the planetary ball mill again. After ball milling at a speed of 2200 rpm to a particle size of 0.06 μm, the material was discharged to obtain a high heat-resistant modifier.
[0038] Step 2: Preparation of heat-resistant borosilicate glass
[0039] The specific formula of the heat-resistant high borosilicate glass is, in parts by weight:
[0040] 76 parts of silicon dioxide,
[0041] 22 parts of boron trioxide,
[0042] 8 parts of sodium oxide,
[0043] 3 parts of aluminum oxide,
[0044] 2 parts of composite flux,
[0045] 1 part of composite clarifier,
[0046] 5 parts of high heat resistance modifier;
[0047] The composite flux is composed of zirconate, sodium fluoroaluminate, lithium borate and nickel boride;
[0048] The zirconate is lithium zirconate;
[0049] The lithium borate salt is lithium metaborate;
[0050] The mass ratio of the zirconate, sodium fluoroaluminate, lithium borate and nickel boride is 40:11:25:7;
[0051] The composite clarifier is composed of molybdate, sodium hexafluoroantimonate, and easily sublimable decomposition products;
[0052] The molybdate is sodium molybdate;
[0053] The easily sublimable decomposition product is molybdenum dioxide;
[0054] The mass ratio of the molybdate, sodium hexafluoroantimonate, and the easily sublimable decomposition product is 45:4:12;
[0055] According to the specific formula of the heat-resistant high borosilicate glass in parts by weight, the corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, and high heat-resistant modifier are weighed, and after preliminary mixing of these powders, they are put into a zirconia crucible, and then the temperature is increased to 1200°C at a rate of 5°C / min and kept warm for 40 minutes, then the temperature is increased to 1820°C at a rate of 3°C / min and kept warm for 2.6 hours, and then the temperature is reduced to 1580°C and kept warm for 25-40 minutes, and then the 1580°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 950°C in advance, and the temperature is maintained at 950°C for annealing. After annealing for 2.6 hours, the temperature is reduced to room temperature at a rate of 3°C / min, and the surface is polished after demolding to obtain the heat-resistant high borosilicate glass.
[0056] Example 2: A method for preparing heat-resistant high borosilicate glass
[0057] Step 1: Preparation of high heat resistant modifier
[0058] Zirconium silicide and sodium zirconium silicate were mixed in a mass ratio of 20:35, and put into a planetary ball mill. The mixture was coarsely ground at a speed of 600 rpm for 60 minutes to obtain a coarse abrasive. The coarse abrasive was dried in an oven at 200°C for 10 hours and then put into the planetary ball mill again. After ball milling at a speed of 1700 rpm to a particle size of 0.01 μm, the material was discharged to obtain a high heat-resistant modifier.
[0059] Step 2: Preparation of heat-resistant borosilicate glass
[0060] The specific formula of the heat-resistant high borosilicate glass is, in parts by weight:
[0061] 66 parts of silicon dioxide,
[0062] Boron trioxide 15 parts,
[0063] 5 parts of sodium oxide,
[0064] 2 parts of aluminum oxide,
[0065] 1 part of composite flux,
[0066] 0.5 parts of composite clarifier,
[0067] 2 parts of high heat resistance modifier;
[0068] The composite flux is composed of zirconate, sodium fluoroaluminate, lithium borate and nickel boride;
[0069] The zirconate is sodium zirconate;
[0070] The lithium borate salt is lithium tetraborate;
[0071] The mass ratio of the zirconate, sodium fluoroaluminate, lithium borate and nickel boride is 10:5:15:3;
[0072] The composite clarifier is composed of molybdate, sodium hexafluoroantimonate, and easily sublimable decomposition products;
[0073] The molybdate is lithium molybdate;
[0074] The easily sublimable decomposition product is aluminum titanate;
[0075] The mass ratio of the molybdate, sodium hexafluoroantimonate, and the easily sublimable decomposition product is 15:2:6;
[0076] According to the specific formula of the heat-resistant high borosilicate glass in parts by weight, the corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, and high heat-resistant modifier are weighed, and after preliminary mixing of these powders, they are put into a zirconia crucible, and then the temperature is increased to 1000°C at a rate of 3°C / min and kept warm for 25 minutes, then the temperature is increased to 1720°C at a rate of 1°C / min and kept warm for 2 hours, then the temperature is reduced to 1500°C and kept warm for 25 minutes, and then the 1500°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 850°C in advance, and the temperature is maintained at 850°C for annealing. After annealing for 2 hours, the temperature is cooled to room temperature at a rate of 1°C / min, and the surface is polished after demolding to obtain the heat-resistant high borosilicate glass.
[0077] Example 3: A method for preparing heat-resistant high borosilicate glass
[0078] Step 1: Preparation of high heat resistant modifier
[0079] Zirconium silicide and sodium zirconium silicate were mixed in a mass ratio of 80:35, and put into a planetary ball mill. The mixture was coarsely ground at a speed of 1600 rpm for 90 minutes to obtain a coarse abrasive. The coarse abrasive was dried in an oven at 260°C for 16 hours and then put into the planetary ball mill again. After ball milling at a speed of 2600 rpm to a particle size of 0.1 μm, the material was discharged to obtain a high heat-resistant modifier.
[0080] Step 2: Preparation of heat-resistant borosilicate glass
[0081] The specific formula of the heat-resistant high borosilicate glass is, in parts by weight:
[0082] 83 parts of silicon dioxide,
[0083] 25 parts of boron trioxide,
[0084] 9 parts of sodium oxide,
[0085] 4 parts of aluminum oxide,
[0086] 4 parts of composite flux,
[0087] 1.5 parts of composite clarifier,
[0088] 6 parts of high heat resistant modifier;
[0089] The composite flux is composed of zirconate, sodium fluoroaluminate, lithium borate and nickel boride;
[0090] The zirconate is lithium zirconate;
[0091] The lithium borate salt is lithium metaborate;
[0092] The mass ratio of the zirconate, sodium fluoroaluminate, lithium borate and nickel boride is 50:19:40:9;
[0093] The composite clarifier is composed of molybdate, sodium hexafluoroantimonate, and easily sublimable decomposition products;
[0094] The molybdate is potassium molybdate;
[0095] The easily sublimable decomposition product is molybdenum dioxide;
[0096] The mass ratio of the molybdate, sodium hexafluoroantimonate, and the easily sublimable decomposition product is 60:8:14;
[0097] According to the specific formula of the heat-resistant high borosilicate glass in parts by weight, corresponding masses of powdered raw materials such as silicon dioxide, boron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, and high heat-resistant modifier are weighed, these powders are preliminarily mixed, and then put into a zirconia crucible, and then the temperature is increased to 1300°C at a rate of 6°C / min and kept warm for 45 minutes, then the temperature is increased to 1860°C at a rate of 4°C / min and kept warm for 3 hours, then the temperature is reduced to 1600°C and kept warm for 40 minutes, and then the 1600°C glass liquid is poured into a graphite mold for molding, the graphite mold is preheated to 1000°C in advance, and the temperature is maintained at 1000°C for annealing. After annealing for 3 hours, the temperature is cooled to room temperature at a rate of 3.5°C / min, and the surface is polished after demolding to obtain the heat-resistant high borosilicate glass.
[0098] Comparative Example 1: Based on Example 1, step 1, preparation of a high heat-resistant modifier, is not performed, and in step 2, 5 parts of the high heat-resistant modifier are replaced by 5 parts of silicon dioxide in equal amounts, and the specific operation is as follows:
[0099] Step 1, preparation of a high heat-resistant modifier is not performed;
[0100] Step 2: Preparation of heat-resistant borosilicate glass
[0101] 5 parts of high heat-resistant modifier were replaced by 5 parts of silicon dioxide, and other operations were the same as in Example 1.
[0102] Comparative Example 2: Based on Example 1, in step 2, in the preparation of heat-resistant high borosilicate glass, zirconate, lithium borate and nickel boride are not added to the composite flux, and 2 parts of the composite flux are replaced by 2 parts of sodium fluoroaluminate in equal amounts. The specific operation is as follows:
[0103] The operation of step 1 is the same as that of embodiment 1;
[0104] Step 2: Preparation of heat-resistant borosilicate glass
[0105] The 2 parts of composite flux were replaced by 2 parts of sodium fluoroaluminate in equal amounts, and the other operations were the same as in Example 1.
[0106] Comparative Example 3: Based on Example 1, in step 2, in the preparation of heat-resistant high borosilicate glass, no molybdate or easily sublimable decomposition product is added to the composite clarifier, and 1 part of the composite clarifier is replaced with 1 part of sodium hexafluoroantimonate. The specific operation is as follows:
[0107] The operation of step 1 is the same as that of embodiment 1;
[0108] Step 2: Preparation of heat-resistant borosilicate glass
[0109] One part of the composite clarifier was replaced by one part of sodium hexafluoroantimonate, and the other operations were the same as in Example 1.
[0110] Performance Test:
[0111] The heat-resistant high borosilicate glass obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 was tested for the following performance indicators:
[0112] Linear thermal expansion coefficient test: Determined according to ASTM E228-2017 "Test method for linear thermal expansion coefficient of solid materials using push rod dilatometer";
[0113] Thermal shock cycle test: The heat-resistant high borosilicate glass obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 was prepared into sheet samples with a diameter of 50 mm and a thickness of 2.8 mm. 50 samples were prepared for each Example and Comparative Example, and thermal shock cycles were performed. The specific operation of the thermal shock cycle was to place the sample in an oven at a constant temperature of 370°C, take it out after 10 minutes, transfer the sample to a cold water tank at a temperature of 20°C within 16 seconds, immerse the sample completely in the cold water tank, and keep it for 30 seconds, then take it out and wipe it dry, repeat the above operation until the sample is broken, and record the number of thermal shock cycles at this time;
[0114] Thermal shock cycle upper limit temperature test: The heat-resistant high borosilicate glass obtained in Examples 1, 2, 3 and Comparative Examples 1, 2, 3 was prepared into sheet samples with a diameter of 50 mm and a thickness of 2.8 mm, and a thermal shock incremental test was performed. 50 samples were used for each thermal shock incremental test. The specific operation method of the thermal shock incremental test was to place the sample in an oven at a constant temperature of 370°C, take it out after 10 minutes, transfer the sample to a cold water tank at a temperature of 20°C within 16 seconds, immerse the sample completely in the cold water tank, and keep it for 30 seconds, then take it out and observe whether the glass is broken. If it is not broken, increase the constant temperature of the oven by 20°C, keep the temperature of the cold water tank unchanged, take a new sample for testing in the same way, until the temperature is raised to the point where the sample is broken, and record the temperature at this time as the upper limit temperature of the thermal shock cycle;
[0115] The above index test data are shown in Table 1:
[0116] Table 1
[0117]
[0118] From the data in Table 1, it can be seen that in Comparative Example 1, no high heat-resistant modifier is added, and the linear thermal expansion coefficient of Comparative Example 1 rises to the maximum, and the number of thermal cycles and the upper limit temperature of thermal shock resistance cycles are reduced to the minimum, which shows that the high heat-resistant modifier plays a vital role in improving the heat resistance of high borosilicate glass; in Comparative Example 2, no zirconate, lithium borate salt, or nickel boride is added to the composite flux. Compared with Example 1, the linear thermal expansion coefficient of Comparative Example 2 is significantly increased, the number of thermal shock resistance cycles is reduced to 23 times, and the upper limit temperature of thermal shock resistance cycles is reduced by 100°C, which shows that the addition of zirconate, lithium borate, and nickel boride, these three substances, can cooperate with sodium fluoroaluminate to further reduce the melting temperature of the main raw materials in the high borosilicate glass formula components when they are melted and the melting temperature after melting. Melt viscosity, thereby promoting the homogenization degree of chemical reaction in the process of glass formation, and finally achieving a significant improvement in the high heat resistance of high borosilicate glass; in Comparative Example 3, no molybdate or easily sublimated decomposition product is added to the composite clarifier. Compared with Example 1, the linear thermal expansion coefficient of Comparative Example 3 increases greatly, and the number of thermal shock resistance cycles and the upper limit temperature of thermal shock resistance cycles are significantly reduced. This shows that molybdate and easily sublimated decomposition product in the composite clarifier components play a vital role in the fusion and rapid discharge of bubbles during the high-temperature melting process of high borosilicate glass. The residual amount of bubbles and the density distribution of residual bubbles have a huge impact on the heat resistance of high borosilicate glass. Therefore, in Comparative Example 3 where no molybdate or easily sublimated decomposition product is added, the decrease in heat resistance is very significant.
[0119] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A heat-resistant high borosilicate glass, characterized in that: The specific formula of the heat-resistant high borosilicate glass is, in parts by weight: 66~83 parts of silicon dioxide, Boron trioxide 15-25 parts, 5-9 parts of sodium oxide, 2~4 parts of aluminum oxide, 1~4 parts of composite flux, 0.5~1.5 parts of composite clarifier, 2~6 parts of high heat resistance modifier; The composite flux is composed of zirconate, sodium fluoroaluminate, lithium borate and nickel boride; The zirconate is one of lithium zirconate and sodium zirconate; The lithium borate salt is one of lithium metaborate and lithium tetraborate; The composite clarifier is composed of molybdate, sodium hexafluoroantimonate, and easily sublimable decomposition products; The molybdate is one of sodium molybdate, lithium molybdate and potassium molybdate; The easily sublimable decomposition product is one of molybdenum dioxide and aluminum titanate; The preparation method of the high heat-resistant modifier is as follows: zirconium silicide and sodium zirconium silicate are mixed in a mass ratio of 20-80:35, and then put into a planetary ball mill, and coarsely grind for 60-90 minutes at a rotation speed of 600-1600 rpm to obtain a coarse abrasive, and the coarse abrasive is placed in an oven at 200-260° C. and dried for 10-16 hours, and then put into the planetary ball mill again, and ball-milled at a rotation speed of 1700-2600 rpm to a particle size of 0.01-0.1 μm, and then discharged to obtain the high heat-resistant modifier.
2. The heat-resistant high borosilicate glass according to claim 1, characterized in that: The mass ratio of the zirconate, sodium fluoroaluminate, lithium borate and nickel boride is 10-50:5-19:15-40:3-9.
3. The heat-resistant high borosilicate glass according to claim 1, characterized in that: The mass ratio of the molybdate, sodium hexafluoroantimonate and the easily sublimable decomposition product is 15-60:2-8:6-14.
4. The method for preparing heat-resistant high borosilicate glass according to claim 1, characterized in that: According to the specific formula of heat-resistant high borosilicate glass in parts by weight, weigh the corresponding mass of silicon dioxide, diboron trioxide, sodium oxide, aluminum trioxide, composite flux, composite clarifier, and high heat-resistant modifier. After the above powdered raw materials are preliminarily mixed, put them into a zirconia crucible, and then heat it to 1000~1300℃ at a rate of 3~6℃ / min and keep it warm for 25~45 minutes, then heat it to 1720℃ at a rate of 1~4℃ / min. ~1860℃ and keep it warm for 2~3 hours, then cool it down to 1500~1600℃ and keep it warm for 25~40 minutes, then pour the 1500~1600℃ glass liquid into the graphite mold for molding, preheat the graphite mold to 850~1000℃ in advance, maintain the temperature of 850~1000℃ for annealing, after annealing for 2~3 hours, cool it down to room temperature at a rate of 1~3.5℃ / min, polish the surface after demolding, and obtain heat-resistant high borosilicate glass.
Citation Information
Patent Citations
Heat-resistant and corrosion-resistant high borosilicate brown glass and preparation method thereof
CN111559863A
Preparation process of high-thermal-property high borosilicate glass product
CN111574050A
Microcrystalline glass using fly ash as main material and preparation method thereof
CN103030295A
Glass-ceramics and glasses
CN111511696A